2013
DOI: 10.1002/cbdv.201200046
|View full text |Cite
|
Sign up to set email alerts
|

Pierisformotoxins A – D, Polyesterified Grayanane Diterpenoids from Pieris formosa and Their cAMP‐Decreasing Activities

Abstract: Four highly acylated diterpenoids, designated as pierisformotoxins A-D (1-4, resp.), along with 26 known compounds, were isolated from the flowers of Pieris formosa. Among them, pierisformotoxins A and B (1 and 2, resp.) were new highly acylated grayanane diterpenoids, of which the five-membered ring A has undergone an oxidative cleavage between C(3) and C(4), followed by lactonization, to give rise to a five-membered lactone ring between C(3) and C(5), differing from the previously reported grayanane diterpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…Ten known diterpenoids ( Figure 2 ), namely, pierisformotoxin C ( 4 ) [ 24 ], secorhodomollolides C ( 5 ), D ( 6 ), and F ( 7 ) [ 28 ], asebotoxins I ( 8 ), II ( 12 ), IV ( 10 ), and VIII ( 11 ) [ 26 , 29 ], pieristoxin I ( 9 ) [ 29 ], and pierisformosin ( 13 ) [ 30 ] were also isolated from P. formosa and were identified by comparison of their spectroscopic data with those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten known diterpenoids ( Figure 2 ), namely, pierisformotoxin C ( 4 ) [ 24 ], secorhodomollolides C ( 5 ), D ( 6 ), and F ( 7 ) [ 28 ], asebotoxins I ( 8 ), II ( 12 ), IV ( 10 ), and VIII ( 11 ) [ 26 , 29 ], pieristoxin I ( 9 ) [ 29 ], and pierisformosin ( 13 ) [ 30 ] were also isolated from P. formosa and were identified by comparison of their spectroscopic data with those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The juice of both its fresh leaves and flowers are used as an insecticide and lotion for the treatment of ring worm and scabies, in folk medicine [ 19 , 20 , 21 ]. More than 60 grayanane diterpenoids with grayanane, 1,5-secograyanane, 3,4- seco -grayanane, 9,10- seco -grayanane, leucothane, 4,5- seco - ent -kauran, and pierisketane carbon skeletons have been isolated from the leaves, flowers, fruits, stems and roots of P. formosa [ 3 , 17 , 22 , 23 , 24 , 25 ]. In our previous work, two new highly esterified 3,4- seco -grayanane diterpenoids, pierisoids A and B, were reported from the flowers of P. formosa [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…S4-S6 †), characteristic of the highly hydroxylated grayanane diterpenoids. Finally, seventeen new 3,4-secograyanoids (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), together with seven known 3,4secograyanoids (18)(19)(20)(21)(22)(23)(24), were isolated from the fractions D1a, D2a, D2b, E1a, E1b, and E2a by a combination of different chromatographic methods. Acetic acid-induced writhing test showed that compounds 1, 2, 4-8, 10-13, and 16-24 exhibited signicant analgesic activity at 5.0 mg kg À1 (ip).…”
Section: Resultsmentioning
confidence: 99%
“…The seven known diterpenoids, namely, secorhodomollolide C (18), 5 pierisoid B (19), 17 secorhodomollolide B (20), 5 secorhodomollolide A (21), 5 pierisformotoxin G (22), 18 pierisformotoxin B (23), 19 and pierisformotoxin A (24), 19 were identied by the comparison of the experimental and previously reported spectroscopic data.…”
Section: Characterization Of Compounds 1-17mentioning
confidence: 99%
See 1 more Smart Citation